2016
DOI: 10.1158/1541-7786.mcr-16-0032
|View full text |Cite
|
Sign up to set email alerts
|

Gas1 Inhibits Metastatic and Metabolic Phenotypes in Colorectal Carcinoma

Abstract: Growth arrest-specific 1 (Gas1) plays a critical role in growth suppression. Previous study indicated that Gas1 was closely associated with survival in patients with colorectal cancer; however, the underlying molecular mechanism remains unclear. In this study, we sought to determine the role of Gas1 in tumorigenesis and metastasis, and elucidate the possible mechanism. First, Gas1 was determined as a negative regulator of oncogenesis and metastasis in colorectal cancer. Mechanistically, Gas1 negatively regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…This is in agreement with other studies demonstrating that Gas1 is capable of initiating apoptosis and inhibiting proliferation [70, 71]. Interestingly, Gas1 exerts similar functions in oncogenesis [63, 72]. Gas1 activity detains tumour growth by inhibiting the proliferation of breast cancer cells [63] and has been reported to play the same mechanistic role in a variety of other cancers; such as colorectal carcinoma [72], papillary thyroid carcinoma [64] and glioma [70].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with other studies demonstrating that Gas1 is capable of initiating apoptosis and inhibiting proliferation [70, 71]. Interestingly, Gas1 exerts similar functions in oncogenesis [63, 72]. Gas1 activity detains tumour growth by inhibiting the proliferation of breast cancer cells [63] and has been reported to play the same mechanistic role in a variety of other cancers; such as colorectal carcinoma [72], papillary thyroid carcinoma [64] and glioma [70].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Gas1 exerts similar functions in oncogenesis [63, 72]. Gas1 activity detains tumour growth by inhibiting the proliferation of breast cancer cells [63] and has been reported to play the same mechanistic role in a variety of other cancers; such as colorectal carcinoma [72], papillary thyroid carcinoma [64] and glioma [70]. In Gas −/− ; Boc −/− PS the CPI was restored to levels observed in Gas +/− ; Boc +/− suggesting that the two genes have opposing roles in regulating cell density.…”
Section: Discussionmentioning
confidence: 99%
“…As positron emission tomography (PET) technology using 18F-fluoro-2-deoxyglucose (FDG) is a manifestation of glycolysis in vivo [16, 17], the SUVmax has been widely used as a surrogate marker for the prognosis of disease in numerous types of cancer, including gastric cancer [18]. To confirm the relationship between Snail and glucose metabolism, we further analyzed the correlation between the Snail IHC staining and the PET/CT SUVmax data from gastric cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that glycolytic enzymes are involved in the EMT process, including FBP1 [10,11,22], PKM2 [23], and LDHA. Glycolytic enzymes are also regulated by classic EMT regulators [11,[24][25][26], so, it is not surprising that PGK1 can regulate the EMT process in breast cancer.…”
Section: Discussionmentioning
confidence: 99%